Topologically Disrupted Gray Matter Networks in Drug-Naïve Essential Tremor Patients With Poor Sleep Quality - Peng, Jiaxin; Yang, Jing; Li, Nannan; Lei, Du; Li, Junying; Duan, Liren; Chen, Chaolan; Zeng, Yan; Xi, Jing; Jiang, Yi; Gong, Qiyong; Peng, Rong (Frontiers in Neurology, 2022)
Abstract Background: Sleep disturbances are widespread among essential tremor (ET) patients and may have adverse effects on patients’ quality of life. However, the pathophysiology underlying poor quality of sleep (QoS) in ET patients remains unclear. Our study aimed to identify gray matter (GM) network alterations in the topological properties of structural magnetic resonance imaging (MRI) related to QoS in ET patients. Method: We enrolled 45 ET patients with poor QoS (SleET), 59 ET patients with normal QoS (NorET), and 66 healthy controls (HC), who underwent a three-dimensional T1-weighted MRI scan. We used a graph-theoretical approach to investigate the topological organization of GM morphological networks, and individual morphological brain networks were constructed according to the interregional similarity of GM volume distributions. Furthermore, we performed network-based statistics, and partial correlation analyses between topographic features and clinical characteristics were conducted. Results: Global network organization was disrupted in ET patients. Compared with the NorET group, the SleET group exhibited disrupted topological GM network organization with a shift toward randomization. Moreover, they showed altered nodal centralities in mainly the frontal, temporal, parietal, and cerebellar lobes. Morphological connection alterations within the default mode (DMN), salience, and basal ganglia networks were observed in the SleET group and were generally more extensive than those in the NorET and HC groups. Alterations within the cerebello-thalamo-(cortical) network were only detected in the SleET group. The nodal degree of the left thalamus was negatively correlated with the Fahn-Tolosa-Marin Tremor Rating Scale score (r = −0.354, p = 0.027). Conclusion: Our findings suggest that potential complex interactions underlie tremor and sleep disruptions in ET patients. Disruptions within the DMN and the cerebello-thalamo-(cortical) network may have a broader impact on sleep quality in patients with ET. Our results offer valuable insight into the neural mechanisms underlying poor QoS in patients with ET.